Monitoring the purification by high‐performance liquid chromatography of cardiotoxins from Naja mossambica mossambica using phase‐sensitive two‐dimensional nuclear magnetic resonance - OTTING, Gottfried; MARCHOT, Pascale; BOUGIS, Pierre E.; ROCHAT, Hervé; WÜTHRICH, Kurt (European Journal of Biochemistry, 1987)
High‐resolution phase‐sensitive two‐dimensional proton nuclear magnetic resonance was used to monitor the preparation by high‐performance liquid chromatography of homogeneous proteins from the venom of Naja mossambica mossambica. This resulted in the characterization of a heterogeneous protein preparation VII2, which had been used in earlier structural studies by NMR, as well as a homogeneous protein CTXIIb and a nearly homogeneous protein fraction CTXIIa, which are now both subject to further investigations of their solution conformations.